Analysis of a Shared Way Set Associative Cache - Hamkalo, José Luis; Cernuschi-Frías, Bruno (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
A new cache memory organization called Shared Way Set Associative (SWSA) is analyzed in this work. The SWSA cache uses two memory banks with different sizes. A placement policy that uses bit map indexing is given for SWSA caches as well as an expression for the associativity. Different LRU related replacement policies are analyzed. The performance of SWSA caches was measured for the SPEC95 benchmarks using trace driven simulations. It was found that SWSA caches of various associatives usually perform better than two-way set associative caches of equivalent size. An analysis of the results using the D3S model is done. Also SWSA caches are compared with victim caches. An additional benefit of SWSA caches is that non power of two total cache sizes may be used. Hence, when SWSA caches are used, a very precise adjustment of the total cache size needed for a given workload is possible. For the SPEC95 benchmarks, savings of 33 percent for the total cache size are obtained with SWSA caches relative to two-way set associative caches that produce nearly the same miss rate.